A High Performance Work Practices Taxonomy: Integrating the Literature and Directing Future Research - Posthuma, Richard A.; Campion, Michael C.; Masimova, Malika; Campion, Michael A. (Journal of management, 2013)
High Performance Work Systems are designed to enhance organizational performance by improving employee capability, commitment, and productivity. Yet there is very little consensus about the structure of these systems and the practices therein. The lack of structure may be inhibiting the growth of knowledge in this field and the degree to which organizations adopt these systems. To address these concerns we develop a comprehensive High Performance Work Practices (HPWPs) taxonomy. We analyzed 193 peer-reviewed articles published over the past 20 years (1992-2011). We classified 61 specific practices into nine categories. We analyze the usefulness of this taxonomy using frequency, time, and countries. Directions for future research are provided.